Differences in Maternal Risk Factors Among Undocumented Latinas in Nebraska by Country of Origin. (December 2018) - Held, Mary L.; Anderson, Kelly; Kennedy, Daniel; Vernon, Elizabeth; Wilkins, Jennifer; Lindley, Lisa C.
Objective: This study compared maternal risk factors by country of origin for 4, 188 Mexican and Guatemalan unauthorized immigrants. Method: Data were drawn from 2007 to 2011 public birth certificate records of unauthorized immigrant mothers residing in Nebraska at the time of delivery. The study sample included 4, 188 women ages 18 years or older and originating from either Mexico or Guatemala. Risk factors, including age risk, preexisting health risks, pregnancy health risks, and prior pregnancy risks, were examined by country of origin. Stata 11.0 was used to compute descriptive statistics and conduct χ 2 test for binary variables and Student t test for continuous variables. Results: Analyses found that Mexican and Guatemalan participants have distinct maternal risk factors. Mexican participants were older and at greater risk of obesity and excessive weight gain during pregnancy, while Guatemalan participants were more likely to receive inadequate prenatal care. Conclusion: Findings suggest that both Mexican and Guatemalan immigrants encounter maternal risk factors that could threaten not only their own health but that of their infants as well. Health and social service providers can tailor education and outreach efforts that are specific to Latina subgroups by origin. Furthermore, targeted strategies to delivering prenatal care to unauthorized immigrants are essential for the well-being of mothers and newborns.